PERTURBATION OF A ROTATIONALLY INVARIANT α-STABLE STOCHASTIC PROCESS BY A PSEUDO-GRADIENT OPERATOR - Osypchuk, M. М.; Boyko, M. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
A generalized fundamental solution of a linear parabolic pseudo-differential equation with a main operator, which is a generator of a rotational-invariant α-stable Markov stochastic process in a multidimensional Euclidean space with α, ranging from 1 to 2 not inclusive, is constructed. A smaller-order operator is a “pseudo-gradient” with a coefficient that is a vector function of one of the classes: bounded continuous or some powerintegrable functions.